Dangerous plants and mushrooms - Allen, Missy; Peissel, Michel, 1937-2011. (New York : Chelsea House Publishers, 1993)
Describes twenty-four dangerous mushrooms and other plants, from aconite to water hemlock.
Includes bibliographical references (p. 117) and index.
Keywords: Poisonous plants -- Juvenile literature; Mushrooms, Poisonous -- Juvenile literature; Dangerous plants -- Juvenile literature; Mushrooms, Poisonous; Poisonous plants; Dangerous plants